PENGETAHUAN IBU TENTANG ASUPAN GIZI PADA BALITA STUNTING: A LITERATUR REVIEW - Risnah, Risnah; Irwan, Muhammad; Evawaty, Evawaty; Masliya, Masliya (Jurnal Midwifery, 2021)
Introduction Toddlers are one of the groups at risk of experiencing nutritional problems. The intake of foods rich in nutrients has a good impact on the growth and development of children. The emergence of nutritional problems in children can be influenced by many factors, one of which is parenting and how the family meets the child's adequate nutritional needs. Stunting (short stature) is a condition in which the body is very short to exceed -2 SD below the median length or height that is the international reference. Stunting describes a state of poor or poor nutrition. The purpose of this review is to determine the relationship between maternal knowledge about nutritional intake in children under five with stunting Method article searches were conducted on the pubmed and google scholar databases. With the keyword knowledge of mothers, nutrition, stunting toddlers. Result the search results were 1705 articles, then screened so that there were 5 articles left Conclusion The results of five studies indicate that there is a relationship between maternal knowledge about nutritional intake in children under five with stunting